2016
DOI: 10.3354/dao03001
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and histologic characterization of coelomatic neoplasms in koi Cyprinus carpio koi

Abstract: Koi carp presenting with coelomatic neoplastic lesions are of growing importance in Switzerland and elsewhere in Europe, as clinical diagnosis is usually difficult and prognosis is usually poor because of late recognition. To gain more information about this condition, between 2008 and 2012, 117 koi diagnosed with coelomatic tumours were included in this study. The nature and growth characteristics of these pathologic tissues were documented. Out of 117 koi, 48.9% (n = 57) were female; the ovary was the most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
(29 reference statements)
2
18
0
Order By: Relevance
“…In the present study, however, the two neoplastic components showed cytomorphological features in accord with pure dysgerminomas and granulosa cell tumours (GCTs) reported in fish by, but not limited to, Ishikawa and Takayama (1978) and Ott‐Knüsel et al. (2016).…”
Section: Antibody Type and Source Methods Antigen Retrieval Primary Asupporting
confidence: 84%
See 3 more Smart Citations
“…In the present study, however, the two neoplastic components showed cytomorphological features in accord with pure dysgerminomas and granulosa cell tumours (GCTs) reported in fish by, but not limited to, Ishikawa and Takayama (1978) and Ott‐Knüsel et al. (2016).…”
Section: Antibody Type and Source Methods Antigen Retrieval Primary Asupporting
confidence: 84%
“…Gonadal tumours are generally considered rare in teleosts, and most of the reported cases have been found in ornamental species (Ott‐Knüsel, Knüsel, Doherr, & Schmidt‐Posthaus, 2016). There are only three reports of spontaneously occurring neoplasms in European seabass Dicentrarchus labrax (Linnaeus, 1758), that is a gastric leiomyoma (Iaria et al., 2020), a multicentric lipoma (Marino, Chiofalo, Mazzullo, & Panebianco, 2011) and a skin fibropapilloma (Ramos & Peleteiro, 2003).…”
Section: Antibody Type and Source Methods Antigen Retrieval Primary Amentioning
confidence: 99%
See 2 more Smart Citations
“…Koi carp ( Cyprinus carpio koi ) are an ornamental variety of common carp frequently kept as pets in domestic ponds worldwide. They have a long lifespan, high economic value and high emotional value as pets due to their tame characters (Ott Knüsel et al., 2016). To date, only a few studies have reported the occurrence of tumours in koi carp, describing neoplasms of the skin, gills, liver, gonads and kidney (Ishikawa & Takayama, 1977; Knüsel et al., 2007; Ott Knüsel et al., 2015, 2016; Sirri et al., 2010, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%